ANALISIS SPASIAL PENYEBARAN PENYAKIT DEMAM BERDARAH DENGUE DENGAN INDEKS MORAN DAN GEARY’S C (STUDI KASUS DI KOTA SEMARANG TAHUN 2011) - Nuril Faiz; Rita Rahmawati; Diah Safitri (Jurnal Gaussian, 2013)
Dengue Haemorrhagic Fever (DHF) is an infectious disease transmitted by the mosquito Aedes aegypti through its the virus dengue virus from patient to another via the bite. Rate dependence dengue in an area estimated to be affected by dengue fever in other neighboring areas. The statement was supported by the First Law of Geography expressed Tobler that all things related to everything else, but near things are more related than distant things. Therefore, if a dengue endemic area, the suspected region make the area immediately adjacent to endemic dengue with a new one. The purpose of this study was to determine whether there is spatial autocorrelation in the spread of dengue fever in the city of Semarang. Limited to methods index and Geary's C Moran and mapping the spread of dengue fever in the city of Semarang with respect to the location (district) in 2011. Of the two methods used showed a pattern of spread of Dengue Hemorrhagic Fever (DHF) are spatially in Semarang and show positive spatial autocorrelation, indicating a nearby location to have similar values, and tend to cluster. Keyword: Dengue Hemorrhagic Fever (DHF), Spatial, Moran Index, Geary’s c.